Macroeconomic Stability, Financial Stability, and Monetary Policy Rules - Pierre-Richard Agenor; Luiz A. Pereira Da Silva (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
This paper reviews arguments for and against attributing explicitly a financial stability objective to monetary policy. The discussion is conducted from the perspective of middle-income countries (MICs), where bank credit plays a critical role both on the supply and demand sides. It also discusses, assuming that a more proactive role is desirable, what monetary policy should react to, to what extent it should be combined with macroprudential regulation (and possibly capital controls), and whether existing models provide adequate benchmarks for studying how these policies interact. The analysis suggests that, on balance, there may be a good case for monetary policy in MICs to go beyond its conventional mandate and address the time dimension of systemic risk—if only during a transitory period, as more is learnt about the implementation and performance of the new macroprudential rules that are currently being discussed.
Keywords: E51; E52; 330